Pengaruh Tugas Kesehatan Keluarga dalam Pencegahan Risiko Jatuh terhadap Kejadian Jatuh pada Lansia - Yuliyanti, Tutik; Dermawan, Deden; Rahayuningsih, Tutik (Indonesian Journal on Medical Science, 2024)
In implementing a fall risk prevention program for elderly members, family health tasks include the ability to recognize the risk of falling, make decisions to prevent the risk of falling, care for members who are sick or need assistance, modify the home environment to prevent the risk of falling and utilize available health facilities. The aim of this research is to analyze the influence of family health duties in preventing the risk of falls on falls in the elderly. The design of this research is a descriptive analytical cross sectional approach with simple linear regression data analysis. This sampling technique was purposive sampling, namely 154 families using a questionnaire as a measuring tool. The research result showed that there was significant influence between family health duties in preventing the risk of falls on the incidence of falls in the elderly. Every 1 increase in the family health task score in preventing the risk of fallas will prevent falls in the elderly by 0.655. The family health task variable in preventing fall risk is able to explain 10.5% of the risk factors for falls in the elderly, while the rest is explained by other variables.Conclusion: the family’s health role in preventing the risk of falls influences the incidence of falls in the elderly. Suggestion:It is hoped that ther is a need for education regarding the implementation of family health duties related to programs to prevent the risk of falls in the elderly.